2009
DOI: 10.1097/nen.0b013e3181a9d524
|View full text |Cite
|
Sign up to set email alerts
|

The Proapoptotic BH3-Only, Bcl-2 Family Member, Puma Is Critical for Acute Ethanol-Induced Neuronal Apoptosis

Abstract: Synaptogenesis in humans occurs in the last trimester of gestation and in the first few years of life whereas it occurs in the postnatal period in rodents. A single exposure of neonatal rodents to ethanol during this period evokes extensive neuronal apoptosis. Previous studies indicate that ethanol triggers the intrinsic apoptotic pathway in neurons and that this requires the multi-BH domain, pro-apoptotic Bcl-2 family member Bax. To define the upstream regulators of this apoptotic pathway, we examined the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 71 publications
4
37
0
Order By: Relevance
“…Quantification of FJB-positive staining revealed WT mice had significant ND in all brain regions in comparison with saline-treated mice and ethanol-treated tPA −/− mice ( Fig. 2 I and J Apoptotic ND induced by ethanol at P7 is mediated by Bax, requires the release of cytochrome c, and culminates with the activation of caspase-3 (7,14,17,18). To determine if activation of ethanol-induced apoptosis after ethanol exposure is tPA dependent, we measured cleaved caspase-3 by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of FJB-positive staining revealed WT mice had significant ND in all brain regions in comparison with saline-treated mice and ethanol-treated tPA −/− mice ( Fig. 2 I and J Apoptotic ND induced by ethanol at P7 is mediated by Bax, requires the release of cytochrome c, and culminates with the activation of caspase-3 (7,14,17,18). To determine if activation of ethanol-induced apoptosis after ethanol exposure is tPA dependent, we measured cleaved caspase-3 by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…As a Bcl-2 homology 3 (BH3)-only family member, PUMA has been implicated as a p53-upregulated modulator of apoptosis (42). It activates Bax, which in turn initiates caspase-3 activation via the intrinsic mitochondrial apoptotic pathway, and this has been shown to be involved in neuronal apoptosis (43,44). Hence, the p53-PUMA-Bax system has been postulated to be a classic signal for the induction of cell death via apoptosis (45).…”
Section: Discussionmentioning
confidence: 99%
“…Puma and Noxa have been implicated to directly and indirectly activate Bax (Bcl-2-associated X protein) and Bak (Bcl-2-antagonist/killer), resulting in permeabilization of the outer mitochondrial membrane, release of cytochrome c and induction of apoptosis [20], [21]. Although both Puma and Noxa have been shown to mediate neuronal cell death, only Puma deficiency was significantly protective against apoptosis, stressing the importance of this factor in the apoptotic cascade [22][24]. With respect to cerebral ischemia, work by Chan and coworkers [25] demonstrated that cerebral ischemia induced Puma upregulation in the hippocampal CA1 region was inhibited by the p53 inhibitor, PFTα, which was correlated with significant neuroprotection.…”
Section: Introductionmentioning
confidence: 99%